Driving anger among motor vehicle drivers in China: A cross-sectional survey. (18th August 2019) - Fei, Gaoqiang; Zhang, Xujun; Yang, Yaming; Yao, Hongyan; Yang, Jie; Li, Xinyu; Gao, Liuwei; Zhou, Yixi; Ming, Wu; Stallones, Lorann; Xiang, Henry
Abstract: Objective: Driving anger is a common emotion while driving and has been associated with traffic crashes. This study aimed to investigate situations that increase driving anger among Chinese drivers. Methods: A cross-sectional study was conducted among 3, 101 drivers in southern China. The translated version of the 33-item Driving Anger Scale (DAS) was used to measure driving anger. Data were collected by face-to-face interviews between June 2016 and September 2016. Results: Confirmatory factor analysis showed that the fit of the original 6-factor model (discourtesy, traffic obstacles, hostile gestures, slow driving, illegal driving, and police presence) was satisfactory, after removing 2 items and allowing 5 error pairs to covary. The model showed satisfactory fit: goodness of fit index (GFI) = 0.90, incremental fit index (IFI) = 0.90, root mean square error of approximation (RMSEA) = 0.06, 90% confidence interval (CI) = 0.061–0.064. Driving anger among Chinese drivers was lower than that in some Western countries. Compared to older and experienced drivers, younger and new drivers were more likely to report driving anger. There was no difference in total reported driving anger between males and females. Additionally, the higher the driver's anger level was, the more likely he or she was to have had a traffic crash. Conclusion: Driving anger is a common emotion among Chinese drivers and has a strong correlation with aggressive driving behavior and traffic crashes.